Multiple opportunistic pathogens can cause a bleaching disease in the red seaweed Delisea pulchra. (15th July 2016) - Kumar, Vipra; Zozaya‐Valdes, Enrique; Kjelleberg, Staffan; Thomas, Torsten; Egan, Suhelen
Summary: While macroalgae (or seaweeds) are increasingly recognized to suffer from disease, in most cases the causative agents are unknown. The model macroalga Delisea pulchra is susceptible to a bleaching disease and previous work has identified two epiphytic bacteria, belonging to the Roseobacter clade, that cause bleaching under laboratory conditions. However, recent environmental surveys have shown that these in vitro pathogens are not abundant in naturally bleached D. pulchra, suggesting the presence of other pathogens capable of causing this algal disease. To test this hypothesis, we cultured bacteria that were abundant on bleached tissue across multiple disease events and assessed their ability to cause bleaching disease. We identified the new pathogens Alteromonas sp. BL110, Aquimarina sp. AD1 and BL5 and Agarivorans sp BL7 that are phylogenetically diverse, distinct from the previous two pathogens and can also be found in low abundance in healthy individuals. Moreover, we found that bacterial communities of diseased individuals that were infected with these pathogens were less diverse and more divergent from each other than those of healthy algae. This study demonstrates that multiple and opportunistic pathogens can cause the same disease outcome for D. pulchra and we postulate that such pathogens are more common in marine systems than previously anticipated.